L'ordre des mots - Arra, Cynthia; Arra, Mélissa (France : Arra, Cynthia ; Arra, Mélissa, 2007)
Far from the usual treatment of transsexual issues, this film, through the choice of its subjects – all contemporary actors and precursors of the trans and intersex movement in France – addresses the gender identity issues head-on by questioning our often unchallenged societal norms and analyzing the nature of the oppression and repression faced by these communities.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films